Silencing the nosocomial pathogen Serratia marcescens by glyceryl trinitrate - Abbas, Hisham A (Afr Health Sci, 2018)
BACKGROUND: Quorum sensing is a cell-to-cell communication system in bacteria that controls the production of virulence factors. Serratia marcescens is a causative agent of hospital-acquired infections that shows high resistance to antibiotics. This makes the treatment of these infections difficult. Quorum sensing regulates the production of virulence factors of S. marcescens such as prodigiosin, protease, swimming and swarming motilities and formation of biofilms. Inhibition of quorum sensing may be an alternative to antibiotic treatment to avoid emergence of resistance. OBJECTIVES: Testing the ability of glyceryl trinitrate to inhibit quorum sensing and virulence factors of Serratia marcescens. METHODS: The inhibiting activities of sub-inhibitory concentration of glyceryl trinitrate against the quorum-sensing regulated violacein pigment in Chromobacterium violaceum CV026 was performed to evaluate the anti-quorum sensing effect of glyceryl trinitrate. The anti-virulence activity was assessed against prodigiosin, protease, biofilm formation in addition to swimming and swarming motilities. RESULTS: Glyceryl trinitrate at at a concentration of 0.25 mg/ml produced significant inhibitory effects against violacein (67.01%), prodigiosin (82.67%), protease, swimming (36.72%) and swarming (79.31%) motilities and biofilm formation (87.83%). CONCLUSION: Glyceryl trinitrate is a quorum sensing and virulence inhibitor that may be useful in treatment of nosocomial infections caused by Serratia marcescens.